Efeito do tratamento térmico nas propriedades físico-mecânicas da madeira de Corymbia citriodora e Eucalyptus saligna - Menezes, Walmir Marques de (2013)
The genera Corymbia and Eucalyptus although used by industries face limitations such as high levels of growth stresses, drying problems and high shrinkage. Thus, methods such as heat treatment are studied to improve these properties. The objective of this research was to study the effect of heat treatment on physical and mechanical properties of wood of Corymbia citriodora and Eucalyptus saligna. From each species 3 trees were sampled, with approximately 40 years of age, which were sectioned with the first two logs in lengths of 3 meters each. The heat treatment was applied with final temperature of 140 º C, 160 º C and 180 º C for 2.5 hours using an oven with forced air circulation. To determine the physical and mechanical properties there were used the procedures of ASTM D 143-94 (ASTM, 2000) and NBR 7190 (ABNT, 1997). The physical properties analyzed were the equilibrium moisture content, weight reduction, loss of density, swelling coefficient, total (linear and volumetric) and coefficient of anisotropy. Mechanical properties evaluated were modulus of elasticity (MOE) and rupture (MOR) in bending, compression parallel to grain and impact resistance. The results, in general, demonstrated for all physical properties that the heat treatment is effective in reducing the hygroscopicity and increasing dimensional stability of both species, with best results in treatments with higher temperatures. The results of the mechanical properties have shown that impact resistance for both species was reduced compared to control in all treatments. The test results static bending, for both species, increased in temperature of 140 ° C and decreased at temperatures of 160 º C and 180 º C. Compression parallel to the grain in wood of Corymbia citriodora increased with heat treatment at temperature of 140 ° C and presented a reduction at other temperatures. The wood of Eucalyptus saligna, the evaluation of compression parallel to the grain, presented a decrease in strength with increasing temperature. In accordance with the results of the study the thermally treated material can be used in places where humidity is higher, however it is not suitable for structural use, because its strength is reduced with increasing temperature.